OPPORTUNITIES OF ANTI B-CELL THERAPY IN MULTIPLE SCLEROSIS - E. P. Evdoshenko; A. L. Maslyancky; L. G. Zaslavsky; A. A. Skoromets; I. S. Ziuzgin; O. E. Riabykina; N. A. Totolian; E. E. Zueva; S. V. Lapin; Areg A. Totolian (Медицинская иммунология)
Abstract. A new role of B-cells in pathogenesis of multiple sclerosis (MS), their relations with B-cells indevelopment of inflammation and probable mechanisms of advanced therapeutic intervention in order to reach B-cell depletion are subject to discussion in present article. Here we describe a clinical case of MS with a resistant clinical course, and results of anti B-cell treatment. To attain maximal clinical effect, a novel therapeutic regimen (a combination of rituximab and mitozantrone) was applied. Clinical, radiological and laboratory methods were used to substantiate the efficiency of treatment.